La réglementation américaine en matière de contrôle des armes chimiques et biologiques - Legault, Albert (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
After identifying the role of the Australia Group which is a multilateral body designed to control export of sensitive chemicals, as well as « equipment » and « technical data » designed to fabricate chemical or bacteriological weapons, this study briefly overviews U.S. policy in terms of export controls, and then attempts to review the current U.S. regulations on chemical and bacteriological weapons. With regard to chemical weapons, the analysis goes back to the Iran-Irak war and traces the evolution of the various controls imposed on chemicals. With the March 13, 1991 decision, export controls exist on 50 chemicals and the warning list has now been reduced to zero. With regards to biological weapons, a whole new list of controls is now being discussed within the Australia Group. A list of 29 countries has been drawn up and the U.S. hope that the Australia Group will adopt similar controls when it meets in December 1991. The article also contains five annexes : the classification of groups countries for export control reasons ; a list of countries under foreign policy controls ; the classification of microorganisms according to their class and degree of pathogenicity; a list of the fifty precursors under control; and the chronological evolution of the U.S. controls imposed on chemicals.